Răspuns :
[tex]\left(66-3\times \:6-\frac{16}{2}\right)-a=\frac{15}{3} \\ 6-3\times \:6-\frac{16}{2}-a=\frac{15}{3} \\ 66-18\times \:-\frac{16}{2}-a=\frac{15}{3} \\ -a-8-18\times \:+66=\frac{15}{3} \\ 58-a-18\times \:=\frac{15}{3} \\ 58-a-18\times \:=5 \\ 58-a=23 \\ a=35[/tex]
( 66 - 3 × 6 - 16 : 2 ) - a = 15 : 3
( 66 - 18 - 8 ) - a = 5
( 48 - 8 ) - a = 5
40 - a = 5
a = 40 - 5
a = 35 → numarul, aflat prin metoda mersului invers
( 66 - 18 - 8 ) - a = 5
( 48 - 8 ) - a = 5
40 - a = 5
a = 40 - 5
a = 35 → numarul, aflat prin metoda mersului invers